Immune classification for the PD-L1 expression and tumour-infiltrating lymphocytes in colorectal adenocarcinoma - Noh, Byeong-Joo (BMC Cancer, 2020)
BACKGROUND: Colorectal adenocarcinoma is the third most common cancer worldwide and a leading cause of cancer-related death. The recent emergence of diverse immunotherapeutic agents has made it crucial to interpret a complex tumour microenvironment intermingled with tumour-infiltrating immune cells to predict the immunotherapeutic response rate. However, in colorectal adenocarcinoma, studies are lacking that provide detailed analyses of programmed death-ligand 1 (PD-L1) and tumour-infiltrating lymphocytes (TIL) to elucidate their prognostic values and to identify immunotherapy-targetable subgroups, preferably with multiple immune-related biomarkers. In the present study, we categorize colorectal adenocarcinomas into four types of tumour immune microenvironments according to PD-L1 expression and TIL, analyse their prognostic values, and propose an immunotherapy-targetable subgroup. METHODS: Formalin-fixed, paraffin-embedded tissue samples of surgically resected primary colorectal adenocarcinomas (n = 489) were obtained and arrayed on tissue microarray blocks. Immunohistochemical stains for PD-L1, programmed cell death protein 1 (PD-1), cluster of differentiation 8 (CD8), and deficient mismatch repair (dMMR) were performed and evaluated. RESULTS: Tumour microenvironment immune type (TMIT) I (PD-L1-positive tumour cells and CD8-high TIL) and type II (PD-L1-negative tumour cells and CD8-low TIL) showed the best and worst prognoses, respectively. PD-L1 overexpression was significantly associated with dMMR status. PD-L1 immunoreactivity was positively correlated with TIL having CD8 or PD-1 overexpression. CONCLUSIONS: TMIT I subgroup showed stronger CD8/PD-L1/PD-1 signalling interaction compared to the other TMIT. Therefore, we propose that the TMIT I subgroup is a candidate TMIT to predict effective response rate for existing immune checkpoint inhibitors and determine targetable subgroups for emerging therapies.